Questioning the Contitutionality of Amandement Aceh’s Autonomy Law by Central Government: Who has the Authority? - Sulaiman, Badri Hasan (SCAD Independent, 2023)
This article criticized the decision of the House of Representatives of the Republic of Indonesia (Dewan Perwakilan Rakyat Republik Indonesia-DPR RI) to amend several articles regarding Aceh's autonomy authorities. The DPR RI should consult the norms of Aceh's autonomy to Aceh's Parliament. Unfortunately, the DPR RI tended to consult and involve Aceh's Parliament before making decisions. Most of the decisions regarding Aceh's autonomy had been decided by the DPR RI, creating a potential conflict of regulation in the year to come and distrust between central and provincial governments. This article used a qualitative method with the black letter law approach concerning some regulations as the primary data. The author claimed that the central government had ignored the principle of checks and balances between the central dan provincial governments and also broke the principle of consultation as stated in Law Number 11 of 2006 concerning the Aceh Government.